Adverse effect of shrimp pond farming effluent to the water quality of Pekan river - Fatin Nur Haziqah, Abd Razak (2018)
Water quality of the Pekan River in Kuantan is influenced by aquaculture activities. This river and its tributaries is important to fisheries and livestock drinking. The characteristics of water quality in Pekan River need to specify because it may affect the water quality of the river. The objectives of this study were to assess the water quality based on National Water Quality Standard (NWQS) and Water Quality Index (WQI) Malaysia and to compare the river water quality before and after the shrimp pond farming effluent being discharged into the river. Water quality of Pekan River is determined based on WQI and NWQS and the samples were collected at three different points and two sampling times. The parameters were divided into two types which were in situ measurement and laboratory measurement. Based on the concentration of pH, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), Ammoniacal Nitrogen (NH-3N) and Total Suspended Solid (TSS), the surface water of the Pekan River was found to be slightly polluted. It shows that the mid-stream of the river was discovered to be more polluted contrast with the downstream and upper stream. In conclusion, the Pekan River is slighty polluted and monitoring and preventing control should be conducted to minimize effect of discharged wastewater from the shrimp pond farming to the water quality of the Pekan River.